2018
DOI: 10.1093/mnras/sty2434
|View full text |Cite
|
Sign up to set email alerts
|

The cataclysmic variable QZ Lib: a period bouncer

Abstract: While highly evolved cataclysmic variables (CVs) with brown dwarf donors, often called "period bouncers", are predicted to make up 40 − 70% of the Galactic CV population, only a handful of such systems are currently known. The identification and characterization of additional period bouncers is therefore important to probe this poorly understood phase of CV evolution. We investigate the evolution of the CV QZ Lib following its 2004 super-outburst using multi-epoch spectroscopy. From time-resolved spectroscopic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 69 publications
(87 reference statements)
0
15
0
Order By: Relevance
“…While this is roughly in agreement with the accretion rates estimated from observations (Townsley & Gänsicke 2009;Pala et al 2017), the theoretical framework outlined above fails to re-produce a number of observational properties of the Galactic population of CVs: (i) the predicted fractions of CVs above and below the period gap ( 1 per cent and 99 per cent, respectively, de Kool 1992; Kolb 1993;Howell et al 2001) are in clear disagreement with the observations (e.g. 23 per cent and 77 per cent, Gänsicke et al 2009, though the observed samples are typically magnitude-limited, and hence biased towards more luminous CVs); (ii) period bouncers are expected to be the main component ( 40 − 70 per cent) of the present-day Galactic CV population but only a small number of such systems has been identified (Patterson et al 2005;Unda-Sanzana et al 2008;Littlefair et al 2006;Patterson 2011;Kato et al 2015Kato et al , 2016McAllister et al 2017;Neustroev et al 2017;Pala et al 2018); (iii) there are clues of the presence of additional AML mechanisms that are not accounted for by the standard model of CV evolution (Patterson 1998; Knigge et al 2011;Schreiber et al 2016;Pala et al 2017;Zorotovic & Schreiber 2017;Belloni et al 2018;Liu & Li 2019), although the physical origin of this enhanced AML is still unclear.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…While this is roughly in agreement with the accretion rates estimated from observations (Townsley & Gänsicke 2009;Pala et al 2017), the theoretical framework outlined above fails to re-produce a number of observational properties of the Galactic population of CVs: (i) the predicted fractions of CVs above and below the period gap ( 1 per cent and 99 per cent, respectively, de Kool 1992; Kolb 1993;Howell et al 2001) are in clear disagreement with the observations (e.g. 23 per cent and 77 per cent, Gänsicke et al 2009, though the observed samples are typically magnitude-limited, and hence biased towards more luminous CVs); (ii) period bouncers are expected to be the main component ( 40 − 70 per cent) of the present-day Galactic CV population but only a small number of such systems has been identified (Patterson et al 2005;Unda-Sanzana et al 2008;Littlefair et al 2006;Patterson 2011;Kato et al 2015Kato et al , 2016McAllister et al 2017;Neustroev et al 2017;Pala et al 2018); (iii) there are clues of the presence of additional AML mechanisms that are not accounted for by the standard model of CV evolution (Patterson 1998; Knigge et al 2011;Schreiber et al 2016;Pala et al 2017;Zorotovic & Schreiber 2017;Belloni et al 2018;Liu & Li 2019), although the physical origin of this enhanced AML is still unclear.…”
mentioning
confidence: 89%
“…In fact, CV accretion discs undergo thermal instabilities called dwarf nova outbursts (Osaki 1974;Meyer & Meyer-Hofmeister 1984;Hameury et al 1998), during which CV systems brighten up to 2-9 mag and these outbursts can last for days up to weeks (Warner 1995;Maza & Gonzalez 1983). Many surveys search the sky nightly for transient events, such as the Catalina Real-time Transient Survey (CRTS, Drake et al 2009), the All-Sky Automated Survey and the All-Sky Automated Survey for Supernovae (ASAS and ASAS-SN, Pojmanski 1997;Shappee et al 2014;Kochanek et al 2017), the Mobile Astronomical System of TElescope Robots (MASTER, Lipunov et al 2010), the Palomar Transient Factory (PTF, Law et al 2009) and the Intermediate PTF (iPTF, Kulkarni 2013), the Asteroid Terrestrialimpact Last Alert System (ATLAS; Tonry et al 2018), the at a distance of 187 pc ( = 5.3 ± 0.3 mas) and is as bright as G = 18.9 mag (Pala et al 2018).…”
Section: Sample Selectionmentioning
confidence: 99%
“…The second branch consists of the period bounce CVs, which are evolving towards longer orbital periods and can be easily recognised as such thanks to their effective temperatures being ≃ 3000 − 4000 K lower than those of the prebounce CVs at similar orbital periods (see the inset in the top panel of Figure 12). We identify seven previously known period bouncers (EG Cnc, Pala et al 2018 andV455 And Patterson 2011) and two new period bounce CVs, SDSS J143544.02+233638.7 and CTCV J1300-3052. The fraction of period bouncers is thus (13 ± 4) per cent, consistent with that derived by Pala et al (2020) from the analysis of a volume-limited sample of CVs (7 − 14 per cent).…”
Section: Mass Accretion Rates and CV Evolutionmentioning
confidence: 99%
“…The accretion flow will heat up the white dwarf again while the period increases. This will slowly drain the brown dwarf and the system ends up as a 'period-bouncer'; a very low accretion rate CV with an orbital period of ≈90 minutes (e.g Pala et al 2018).…”
Section: Formation Historymentioning
confidence: 99%